Validation of Zero TE–MRA in the Characterization of Cerebrovascular Diseases: A Feasibility Study - Shang, S. (AJNR Am J Neuroradiol, 2019)
BACKGROUND AND PURPOSE: Zero TE–MRA is less sensitive to field heterogeneity, complex flow, and acquisition noise. This study aimed to prospectively validate the feasibility of zero TE–MRA for cerebrovascular diseases assessment, compared with TOF-MRA. MATERIALS AND METHODS: Seventy patients suspected of having cerebrovascular disorders were recruited. Sound levels were estimated for each MRA subjectively and objectively in different modes. MRA image quality was estimated by 2 neuroradiologists. The degree of stenosis (grades 0–4) and the z-diameter of aneurysms (tiny group ≤3 mm and large group >3 mm) were measured for further quantitative analysis. CTA was used as the criterion standard. RESULTS: Zero TE–MRA achieved significantly lower subjective perception and objective noise reduction (37.53%). Zero TE–MRA images showed higher signal homogeneity (3.29 ± 0.59 versus 3.04 ± 0.43) and quality of venous signal suppression (3.67 ± 0.47 versus 2.75 ± 0.46). The intermodality agreement was higher for zero TE–MRA than for TOF-MRA (zero TE, 0.90; TOF, 0.81) in the grading of stenosis. Zero TE–MRA had a higher correlation than TOF-MRA (zero TE, 0.84; TOF, 0.74) in the tiny group and a higher consistency with CTA (intraclass correlation coefficient, 0.83; intercept, −0.5084–1.1794; slope −0.4952 to −0.2093) than TOF-MRA (intraclass correlation coefficient, 0.64; intercept, 0.7000–2.6133; slope −1.0344 to −0.1923). Zero TE–MRA and TOF-MRA were comparable in the large group. Zero TE–MRA had more accurate details than TOF-MRA of AVM and Moyamoya lesions. CONCLUSIONS: Compared with TOF-MRA, zero TE–MRA achieved more robust performance in depicting cerebrovascular diseases. Therefore, zero TE–MRA was shown to be a promising MRA technique for further routine application in the clinic in patients with cerebrovascular diseases.